Development and feasibility of need-based yoga program for family caregivers of in-patients with schizophrenia in India - Jagannathan, Aarti (Medknow Publications & Media Pvt Ltd, 2012)
CONTEXT AND AIM: Yoga has been found to be effective in the management of stress. This paper describes the development of a yoga program aimed to reduce burden and improve coping of family caregivers of inpatients with schizophrenia in India. MATERIALS AND METHODS: Based on the assessment of caregiver needs, literature review, and expert opinion, a ten-day group yoga program was initially developed using the qualitative inductive method of inquiry. Each day's program included warm-up exercises, yogic asanas, pranayama, and satsang. A structured questionnaire eliciting comments on each day's contents was given independently to ten experienced yoga professionals working in the field of health for validation. The final version of the program was pilot-tested on a group of six caregivers of in-patients with schizophrenia admitted at NIMHANS, Bangalore. RESULTS: On the question of whether the program would help reduce the burden of caregivers, six of the ten experts (60%) gave a rank of four of five (very much useful). Based on comments of the experts, several changes were made to the program. In the pilot-testing stage, more than 60% of the caregivers assigned a score of four and above (on a five-point Likert scale, five being extremely useful) for the overall program, handouts distributed, and performance of the trainer. Qualitative feedback of the caregivers further endorsed the feasibility and usefulness of the program. CONCLUSION: The developed yoga program was found to be acceptable to caregivers of in-patients with schizophrenia.